Physiological Characteristics of Cotton Subtending Leaf Are Associated With Yield in Contrasting Nitrogen-Efficient Cotton Genotypes - Iqbal, Asif; Jing, Niu; Qiang, Dong; Xiangru, Wang; Huiping, Gui; Hengheng, Zhang; Nianchang, Pang; Xiling, Zhang; Meizhen, Song (Frontiers in Plant Science, 2022)
Nitrogen (N) plays an important role in various plant physiological processes, but studies on the photosynthetic efficiency and enzymatic activities in the cotton subtending leaves and their contribution to yield are still lacking. This study explored the influence of low, moderate, and high N levels on the growth, photosynthesis, carbon (C), and N metabolizing enzymes, and their contribution to yield in CCRI-69 (N-efficient) and XLZ-30 (N-inefficient). The results showed that moderate to high N levels had significantly improved growth, photosynthesis, and sucrose content of CCRI-69 as compared to XLZ-30. The seed cotton yield and lint yield of CCRI-69 were similar under moderate and high N levels but higher than XLZ-30. Similarly, moderate to high N levels improved the C/N metabolizing enzymatic activities in the subtending leaf of CCRI-69 than XLZ-30. A strong correlation was found between subtending leaf N concentration with C/N metabolizing enzymes, photosynthesis, sucrose contents, boll weight, and seed cotton yield of N-efficient cotton genotype. These findings suggest that subtending leaf N concentration regulates the enzymatic activities and has a key role in improving the yield. These parameters may be considered for breeding N-efficient cotton genotypes, which might help to reduce fertilizer loss and improve crop productivity.